The Use of English Relative Clauses by Indonesian Authors: A Case Study in Business, Engineering, and Science Journal Articles - Sutrisno, Adi; Denistia, Karlina (Journal of Language and Literature, 2024)
The ability to effectively use relative clauses is pivotal in English journal articles, as it allows authors the flexibility to modify various noun phrases within sentences to convey clearer and more precise writing. This research explores the strategies employed by Indonesian authors from three distinct disciplines - business, engineering, and science. To accomplish this, we analyzed thirty papers published in Electrical Engineering and Computer Science, Makara Journal of Science, and Gadjahmada International Journal of Business. In total, 1453 relative clauses were collected and analyzed. A cross-classification analysis was performed to examine the distribution of relative clauses. The findings of the study indicate a preference among Indonesian writers to use non-reduced relative clauses, specifically those that serve as restrictive modifiers for objects. We also observe that the past participle is employed with greater frequency than the present participle. The results reveal that Indonesian authors prefer non-reduced relative clauses over reduced ones, opt for restrictive clauses over non-restrictive ones, and consistently favor relativizing the subject (S-form) in their relative clauses over the object (O-form). Our results also show that the choice of relative clauses is subject-specific, influenced by the distinct communicative requirements and preferences within each field. Our examination of relative clauses has provided insights into the syntactic choices, including their reduction status, restrictiveness, the use of participles, connectors, and the syntactic category modified by the clause.